2009
DOI: 10.1038/ncb0509-510
|View full text |Cite
|
Sign up to set email alerts
|

Virus entry by macropinocytosis

Abstract: As obligatory intracellular parasites, viruses rely on host-cell functions for most aspects of their replication cycle. This is born out during entry, when most viruses that infect vertebrate and insect cells exploit the endocytic activities of the host cell to move into the cytoplasm. Viruses belonging to vaccinia, adeno, picorna and other virus families have been reported to take advantage of macropinocytosis, an endocytic mechanism normally involved in fluid uptake. The virus particles first activate signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
944
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 738 publications
(976 citation statements)
references
References 125 publications
25
944
1
6
Order By: Relevance
“…In summary, we observed that closely related virus particles were capable of eliciting different macropinocytic programs in the same cells. It is known that macropinocytosis can differ between cells (36), but here two distinct responses were observed in the same cells. The plasticity of VACV and its interaction with host cells revealed by our observations demonstrated that the virus is capable of exploiting a repertoire of alternative host-cell responses.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, we observed that closely related virus particles were capable of eliciting different macropinocytic programs in the same cells. It is known that macropinocytosis can differ between cells (36), but here two distinct responses were observed in the same cells. The plasticity of VACV and its interaction with host cells revealed by our observations demonstrated that the virus is capable of exploiting a repertoire of alternative host-cell responses.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a number of viruses have been shown to use MPC, or MPC-like entry pathways for infection (reviewed by Mercer & Helenius, 2009). MPC is especially active in specialized antigen-presenting cells, such as macrophages and DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Macropinocytosis is a triggered process involving complex signaling and vigorous, cell‐wide actin ruffling leading to plasma membrane protrusions. The ruffles can take the form of circular projections, lamellipodia and blebs 15. Macropinosomes are large, fluid‐filled, cytoplasmic vacuoles formed by membrane fission when the protrusions collapse back onto the plasma membrane 16.…”
mentioning
confidence: 99%
“…To date, over 20 different viruses from diverse families have been shown to use macropinocytosis for infectious entry (reviewed in 15 31). Amongst these is vaccinia virus (VACV), a large, enveloped, dsDNA virus characterized by its structural complexity and cytoplasmic life cycle.…”
mentioning
confidence: 99%